The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.2134/jeq2016.08.0304
|View full text |Cite
|
Sign up to set email alerts
|

Urea Release by Intermittently Saturated Sediments from a Coastal Agricultural Landscape

Abstract: Urea-N is linked to harmful algal blooms in lakes and estuaries, and urea-N-based fertilizers have been implicated as a source. However, the export of urea-N-based fertilizers appears unlikely, as high concentrations of urea-N are most commonly found in surface waters outside periods of fertilization. To evaluate possible autochthonous production of urea-N, we monitored urea-N released from drainage ditch sediments using mesocosms. Sediments from a cleaned (recently dredged) drainage ditch, uncleaned ditch, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 56 publications
5
20
0
Order By: Relevance
“…In Palmetto Branch, urea-N had similar directional associations with temperature and DOC: DON, but the relationships were weak and not statistically significant (Figure 7e,7f). In the drainage ditch, we found a strong positive effect of temperature on urea-N concentrations (Figure 7g; p < 0.01), which agreed with a recent microcosm study of urea-N production in ditch sediments from Maryland's Lower Eastern Shore (King et al 2017). In contrast, urea-N levels in ditches displayed a weak, negative relationship with DOC:DON (Figure 7h), which was directionally consistent with the other sites, but not statistically significant (p = 0.26).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…In Palmetto Branch, urea-N had similar directional associations with temperature and DOC: DON, but the relationships were weak and not statistically significant (Figure 7e,7f). In the drainage ditch, we found a strong positive effect of temperature on urea-N concentrations (Figure 7g; p < 0.01), which agreed with a recent microcosm study of urea-N production in ditch sediments from Maryland's Lower Eastern Shore (King et al 2017). In contrast, urea-N levels in ditches displayed a weak, negative relationship with DOC:DON (Figure 7h), which was directionally consistent with the other sites, but not statistically significant (p = 0.26).…”
supporting
confidence: 91%
“…Interestingly, all four sites showed some effects of temperature and DOC:DON ratios on urea-N concentrations, although some relationships were not statistically significant. In the drainage ditch, we found a strong positive effect of temperature on urea-N concentrations (Figure 7g; p < 0.01), which agreed with a recent microcosm study of urea-N production in ditch sediments from Maryland's Lower Eastern Shore (King et al 2017). In Palmetto Branch, urea-N had similar directional associations with temperature and DOC: DON, but the relationships were weak and not statistically significant (Figure 7e,7f).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Comparison of mesocosm and bioassay findings suggested that urea lacked the toxic effects of NH4+ observed in cool waters (Glibert et al., 2016; Swarbrick et al., 2019), in part because of limited hydrolysis of urea during spring and late autumn. Overall, growth stimulation by urea was consistent with previous short‐term laboratory (Belisle et al., 2016; Berman & Chava, 1999; Yuan et al., 2012) and mesocosm experiments (Bogard et al., 2020; Donald et al., 2011; Finlay et al., 2010), but showed that phytoplankton growth was strongly enhanced in spring, when urea influx is expected to be elevated (Bogard et al., 2012; Glibert et al., 2006) and temperature‐dependent enzymatic hydrolysis to NH 4 + is low (King et al., 2017; Siuda & Chrόst, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary research suggests that effects of urea on water quality in P‐rich lakes may vary among seasons (Belisle et al., 2016; Mitamura, Tachibana, Konda, Ueda, & Seike, 2010; Siuda & Kiersztyn, 2015). First, export of urea is expected to be highly seasonal (Glibert et al., 2006; King et al., 2017), particularly in northern regions where agricultural fertiliser application and release of wastewater lagoon effluents tend to occur in spring and autumn, when low temperatures coincide with reduced microbial and enzymatic activity (Siuda & Chrόst, 2006) and elevated runoff (Pham, Leavitt, McGowan, Wissel, & Wassenaar, 2009; Pomeroy et al., 2007). Together, these factors reduce the extent of urea hydrolysis and favour export to lakes (Di & Cameron, 2008; Silva, Cameron, Di, & Jorgensen, 2005; Swensen & Singh, 1997).…”
Section: Introductionmentioning
confidence: 99%